Cadmium telluride thin -film solar cell - DENG GUOYUN; LI YIMING (2016)
The utility model discloses a cadmium telluride thin -film solar cell, including the base plate, from the base plate toward stacking gradually barrier layer, transparent conducting film, first buffer layer, second buffer layer, window layer, cadmium telluride light absorbing zone, back of the body contact layer outward. The utility model discloses a set up first buffer layer and second buffer layer on transparent conducting film, this helps the better cover substrate surface in window layer, first buffer layer and second buffer layer have the high resistivity, and this can prevent the inside leakage of battery, improve the performance of cadmium telluride hull cell. 本实用新型公开了种碲化镉薄膜太阳能电池，包括基板，从基板往外依次层叠阻挡层、透明导电层、第缓冲层、第二缓冲层、窗口层、碲化镉光吸收层、背接触层。本实用新型通过在透明导电层上设置第缓冲层和第二缓冲层，这有助于窗口层更好的覆盖基板表面；所述第缓冲层和第二缓冲层具有高电阻率，这可以防止电池内部的泄漏，提高碲化镉薄膜电池的性能。